The roles of self-efficacy and metacognition in reading comprehension among Saudi EFL learners - Shehzad, Muhammad Waleed (2019)
The reading comprehension of Saudi learners is generally unsatisfactory when they enroll in universities. However, empirical research on the relationship between self-efficacy sources and reading comprehension is scarce in the EFL context. Furthermore, there is limited research on the relationship between metacognitive reading strategies and reading comprehension using reading self-efficacy as a mediator. This study aimed to identify the hierarchical order of self-efficacy sources and metacognitive reading strategies. Additionally, it intended to determine the level of reading self-efficacy and reading comprehension. Moreover, this study proposed that reading self-efficacy beliefs might mediate the relationship between self-efficacy sources, metacognitive reading strategies, and reading comprehension. The current study employed a mixed-methods correlational research design in which quantitative data using questionnaires was collected by employing proportionate stratified random sampling from 383 Saudi EFL learners. Besides, qualitative data was gathered through semi-structured interviews with six Saudi EFL learners using homogeneous purposeful sampling. Findings indicated that ‘mastery experience’ was the most reported self-efficacy source, whereas ‘physiological state’ was least reported. Furthermore, ‘global strategies’ was the most reported metacognitive reading strategy, in contrast to ‘support strategies’ which was least reported. Additionally, the majority of the students had a higher level of reading self-efficacy. Also, regarding the reading comprehension level, most of the learners were ‘above average’ readers. Reading self-efficacy beliefs mediated the relationship between all the self-efficacy sources and reading comprehension except ‘physiological state’. Moreover, reading self-efficacy beliefs mediated the relationship between metacognitive reading strategies and reading comprehension. The qualitative findings revealed several factors that were responsible for the influence of self-efficacy sources/metacognitive reading strategies on reading comprehension such as the role of teachers, competitive environment, confidence, time constraints, skimming, visualising, and notes-taking. The findings offer several implications for EFL teachers and policy makers which could prove beneficial for EFL learners in terms of increasing their self-efficacy and improving their metacognitive strategies in reading comprehension.